2007
DOI: 10.1523/jneurosci.2121-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Glucocorticoids Increase Hippocampal Vulnerability to Neurotoxicity under Conditions That Produce CA3 Dendritic Retraction But Fail to Impair Spatial Recognition Memory

Abstract: We previously found that chronic stress conditions producing CA3 dendritic retraction and spatial memory deficits make the hippocampus vulnerable to the neurotoxin ibotenic acid (IBO). The purpose of this study was to determine whether exposure to chronic corticosterone (CORT) under conditions that produce CA3 dendritic retraction would enhance CA3 susceptibility to IBO. Male Sprague Dawley rats were chronically treated for 21 d with CORT in drinking water (400 g/ml), and half were given daily injections of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 41 publications
(50 reference statements)
2
81
0
3
Order By: Relevance
“…Histological quantification, involving the measurement of CA3 or amygdala dendritric branch length for selected neurons, was performed with AxioVision 4.7 software and a Zeiss Imager M1 microscope. For each rat, total dendrite length was measured for amygdala neuron and separately for the apical branch and the basal sections of the CA3 neuron, as described by McLaughlin et al (2005) and Conrad et al (2007). We selected three to five hippocampal neurons per rat for measurement by an investigator blind to the origin of the experimental animal.…”
Section: Golgi Stainingmentioning
confidence: 99%
“…Histological quantification, involving the measurement of CA3 or amygdala dendritric branch length for selected neurons, was performed with AxioVision 4.7 software and a Zeiss Imager M1 microscope. For each rat, total dendrite length was measured for amygdala neuron and separately for the apical branch and the basal sections of the CA3 neuron, as described by McLaughlin et al (2005) and Conrad et al (2007). We selected three to five hippocampal neurons per rat for measurement by an investigator blind to the origin of the experimental animal.…”
Section: Golgi Stainingmentioning
confidence: 99%
“…All brains were removed and processed at the same time (72 hours following the last injection). The staining procedure was the same as described previously by our lab (Bellani et al, 2006;Conrad et al, 2007;Kleen et al, 2006;McLaughlin et al, 2005;McLaughlin et al, 2007).…”
Section: Golgimentioning
confidence: 99%
“…Several lines of evidence indicate that prolonged elevation of glucocorticoid makes the hippocampus vulnerable to neurotoxic challenges (12,13). In addition to the finding that an acute treatment with TMT temporally increases the concentration of plasma corticosterone in rats (14), it has been demonstrated that a reduction in the level of circulating corticosterone by metyrapone, an inhibitor of corticosterone synthesis, prevents TMT from damaging the hippocampal neurons and eliciting learning impairment and hyperactivity in rats (15).…”
Section: Introductionmentioning
confidence: 99%